Height in Twentieth-Century Chilean Men: Growth with Divergence - Droller, F (Springer Science and Business Media Deutschland GmbH, 2021)
This article provides the first series of Chilean adult male height for the whole of the twentieth century. The height of adult males increased by about 5.5 cm during the twentieth century, primarily during the second half of this period. This is the greatest improvement in biological welfare in Chilean history; Chilean males have never been as tall as they are today. Using a sample of around 36,371 individuals, we document the evolution of the average height of Chilean soldiers (male) born from the 1900s to the 1990s. This sample can be safely taken as a good proxy of the average height of Chilean male population for the period under study. We provide an explanation of both the main determinants of physical stature and the rapid increase in height in Chile over this period. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.